Two-Dimensional Nature and the Meaning of the Density of States in Redox Monolayers - Feliciano, Gustavo T. [UNESP]; Bueno, Paulo R. [UNESP] (American Chemical Society (ACS), 2020)
It has been suggested that the transport of charge in molecular electronics and redox junctions is, at the sub-nanoscale, that is, for dimensions lower than 5 nm, fundamentally related [Phys. Chem. Chem. Phys, 2020, 10.1039/D0CP01621G]. In the present work, supported on conceptual and computational methods of density functional theory, we provided additional evidence for this relationship, by showing that redox molecular structures assembled over conductive electrodes resemble, in terms of their electrochemical DOS, 2DEG structures. Owing to the fact that 2DEG structures are commonly taken as the fundamental physical model applied in the designing of field-effect transistors, an electrochemical versionis important as a blueprint for the development of devices required in electrochemical environments. Additionally, the effect of the dielectrics of the solvent and of the counter ions over the electrochemical 2D DOS of redox molecular films was studied using hybrid computational methods. The results of computational simulation of the DOS were qualitatively compared with those obtained experimentally.